Translating a Portuguese poem in LIBRAS. Linguistic considerations and form-focused tasks. (Belas Infiéis, 2019)
AbstractThe teacher of deaf children in primary education is called to apply sign bilingualism in his/her teaching, and hence to use sign language - such as LIBRAS - as the first language during in-class time, and as a school subject. This again means that all other subjects - among them Portuguese - need to be taught in SL. In fact, Portuguese is taught as the second language of deaf children. In such educational setting, the teacher needs to develop learning materials for LIBRAS. Current research lacks recording such practices, although, unofficially, it is common knowledge that teachers translate existing school materials that have been developed for Portuguese and for hearing pupils in primary education. In this paper, a LIBRAS translation is presented of the poem “As abelhas” by Vinícius de Moraes, with the scope to demonstrate its linguistic use for the teaching of LIBRAS as a first language. Apart from its target vocabulary items, form-focused tasks are demonstrated, indicating their implementation for the development of deaf children’s receptive and productive skills. In doing so, the poem is presented following the A-level descriptors (A1, A2) of the Common European Framework of Reference for Sign Languages.